2017
DOI: 10.1111/mec.14186
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of the pine weevil degrades conifer diterpenes and increases insect fitness

Abstract: The pine weevil (Hylobius abietis), a major pest of conifer forests throughout Europe, feeds on the bark and cambium, tissues rich in terpenoid resins that are toxic to many insect herbivores. Here, we report the ability of the pine weevil gut microbiota to degrade the diterpene acids of Norway spruce. The diterpene acid levels present in ingested bark were substantially reduced on passage through the pine weevil gut. This reduction was significantly less upon antibiotic treatment, and supplementing the diet w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(108 citation statements)
references
References 70 publications
(133 reference statements)
4
104
0
Order By: Relevance
“…If we assume that the number of eggs in a nest upon collection reflects a queen's fecundity, then our results indicate that a queen's abdominal microbiome might affect her egg production and ultimately colony fitness. This is in line with other studies on insects, which found that bacterial gut residents can influence egg production (e.g., Ben-Yosef, Pasternak, Jurkevitch, & Yuval, 2014;Berasategui et al, 2017;Rosengaus et al, 2011). However, our observation could be confounded by factors such as diet, health, and genetics.…”
Section: Abdominal Microbiome Characteristics and Colony Phenotypesupporting
confidence: 92%
“…If we assume that the number of eggs in a nest upon collection reflects a queen's fecundity, then our results indicate that a queen's abdominal microbiome might affect her egg production and ultimately colony fitness. This is in line with other studies on insects, which found that bacterial gut residents can influence egg production (e.g., Ben-Yosef, Pasternak, Jurkevitch, & Yuval, 2014;Berasategui et al, 2017;Rosengaus et al, 2011). However, our observation could be confounded by factors such as diet, health, and genetics.…”
Section: Abdominal Microbiome Characteristics and Colony Phenotypesupporting
confidence: 92%
“…Across the seven treatments, developmental time and insect weight upon adult emergence were not significantly different ( Fig. 4a and b) (Friedman test: developmental time, 2 [6] ϭ 5.282, P ϭ 0.508; weight at emergence, 2 [6]…”
Section: C-lys Gfp C-lysmentioning
confidence: 99%
“…Gordonibacter,2 [6] ϭ 4.041, P ϭ 0.671; Klebsiella, 2 [6] ϭ 12.143, P ϭ 0.059).Similarly, adults that emerged from the dsRNA-treated nymphs showed minor changes in the bacterial community, with only Hungatella sp. showing statistically…”
mentioning
confidence: 99%
“…Single studies used groEL (Monochamus alternatus, Aikawa et al, 2009; Tribolium madens, Fialho & Stevens, 2000) or ITS genes (Tribolium madens, Fialho & Stevens, 2000). So far, only five studies have used next-generation sequencing technology (Illumina or 454) to detect Wolbachia; two used 16S rDNA for metabarcoding of microbiota (Sitona obsoletus, Steriphus variabilis, White et al, 2015; Aleochara bilineata and Aleochara bipustulata, Bili et al, 2016; Hylobius abietis, Berasategui et al, 2016;Brontispa longissimi, Takano et al, 2017; Harmonia axyridis, Dudek et al, 2017) and one used shotgun genomic sequencing (Amara alpine, Heintzman et al, 2014). For genotyping of hosts, 52.4% of studies utilized fragments of COI from mtDNA (usually a barcode fragment of this gene).…”
Section: Examined Genetic Markersmentioning
confidence: 99%